Who is more eager to use gamification in economic disciplines? Comparison of students and educators - Nikolina Dečman; Ana Rep; Marion Titgemeyer (Business Systems Research (BSR), 2022)
Background: In this paper, the focus is on the application of digital and mobile technologies as supporting tools for the implementation of gamification in the field of education of future economists. Objectives: The paper's main objective is to explore whether educators and students are motivated and willing to apply additional technologies as main gamification components in their work and education. Moreover, the paper aims to assess how their more comprehensive application affects the quality of teaching, work flexibility, new learning opportunities, and outcomes. Methods/Approach: The survey method was used to collect answers from educators and students primarily interested in accounting, finance, trade and tourism from higher and secondary education institutions in Croatia, Poland, Serbia and Germany. Afterwards, the responses were compared using statistical methods. Results: Research results confirm that educators and students are willing to use gamification in teaching. Still, they also expressed the need for better administrative support in using particular e-learning tools. Surprisingly, educators are more eager to use gamification in their work than students. Conclusions: The study's general conclusion is that educators and students are both aware of the advantages of using e-learning tools provided through digital and mobile technologies and are eager to implement more gamification in the teaching process. However, continuous education in applying new digital technologies is needed on both sides.
Keywords: A20; I21; O33; 330; Gamification; digital technologies; mobile technologies; teaching process; students; educators; secondary education; higher education; economic disciplines